Phenomenological Study of Game Tactics in Male and Female Volleyball Athletes - Mohamad Rizki; Tatang Muhtar; Muhammad Nur Alif (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aimed to understand the tactical playing ability of male and female vol-leyball athletes at O2C Ciparay Volleyball Academy. Using a qualitative phenome-nological design, the research explored athletes' interpretations of game reading, decision-making, communication, and strategic adjustment. Eight participants-three male athletes, three female athletes, and two coaches-were selected through purposive sampling based on active training participation, minimum three years of experience, involvement in official competitions, and willingness as in-formants. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using NVivo. Findings indicate that tactical abil-ity is influenced by decision-making, game pattern reading, psychological factors, team communication, mastery of basic techniques, positioning, covering, ball an-ticipation, training experience, and gender differences in playing characteristics. Athletes who effectively read game situations, communicate, and master basic techniques tend to make quicker, more appropriate decisions in attacking and de-fensive situations, Differences between male and female athletes are influenced by physical aspects, anthropometry, power, endurance, and training approaches. This study concludes that tactical ability is essential for volleyball performance and requires development through technical training, game-situation training, mental strengthening, communication, and teamwork, Coaches should design in tegrated, contextual, and gender-responsive training programs to optimize tactical development across competition levels.